Dampak Perkembangan Teknologi Terhadap Perilaku Dan Kehidupan Pemuda Pemudi Di Era Milenial - Isti'anatul Mashlahah; Syamsul Arifin (Jurnal Pengabdian Masyarakat dan Penerapan Ilmu Pengetahuan, 2023)
The rapid development of technology has led to the emergence of the millennial era where technology has become the need of every individual, especially young people in the millennial era who are dealing with technological advances, so they are required to always sort out any information they get, in order to prevent adverse effects due to access between worlds. easy to obtain so that it can become a weapon for irresponsible people to attack a territory from the next generation. The purpose of this research is to find out the various impacts of technological developments, especially for teenagers, so that we as teenagers and parents can minimize unwanted things from the impact of technological developments in this millennial era. In this study, the authors used the literature study method, namely the data obtained from examining various sources related to the issues to be discussed. The author uses sources in the form of journals which certainly discuss the impact of technological developments in the millennial era. This research found that technology has positive and negative effects on people's behavior and life in the millennial era, especially for teenagers. One of the influences of technology in the millennial era is the fading of local culture because of the inclusion of foreign culture which is considered more modern for teenagers, besides that there is also a positive impact in the form of easy access between worlds which makes it easier for teenagers in the process of learning and obtaining information.